VolcanoGasML: a format to exchange geochemical volcanic gases data - Eric Reiter (Data Science Journal, 2007)
Chemical analyses of volcanic gases consist of: location of sampling, date of sampling, identification of the sampling, etc. Nowadays, these data are generally represented in different formats. All of these formats are inflexible and machine dependent. XML has become the most important method of transferring data between computers. VolcanoGasML is a new format, based on XML, for the chemical analyses of volcanic gases. Its definition is divided into several layers: the first one describes the general information concerning the sample, the second, which is organized in several sublayers, contains the chemical data.